Defining observable practice activities for postgraduate residents in cytopathology - Sana Ahuja; Nadeem Tanveer; Vinod Kumar Arora (Wolters Kluwer Medknow Publications, 2022)
Competency-based medical education (CBME) is the new buzzword in the context of the Indian postgraduate teaching. Entrustable professional activities (EPA) are a means by which competencies can be converted to clinical practice. The National Medical Council (NMC) has outlined the four basic skills expected from postgraduate students at the end of cytopathology training. In pathology, the College of American Pathologists Graduate Medical Education Committee has defined 19 EPA s for pathology postgraduate education. Out of these, 4 were for clinical pathology, 7 were for anatomic pathology, and 8 related to both of the above. However, both NMC and College of American Pathologists (CAP) have not further divided the EPAs and skills into smaller observable components observable practice activities (OPAs) so that the postgraduates can have clear-cut targets for their competency. Integration of the EPA to the pathology curriculum would be easier if separate OPAs are devised for postgraduates. We provide the proposed OPAs in cytopathology for postgraduate students based on multiple rounds of analysis by faculty from different institutions using a modified Delphi approach. This study is an example of a pilot project undertaken to implement OPAs in cytopathology laboratory by taking feedback from the stakeholders. This was followed by mapping these OPAs to their relevant competencies. These can be considered stepping stones for the final competency evaluation. To conclude, shortlisting the OPAs is the first step in integrating CBME into the existing pathology postgraduate teaching. The next step is to devise ways to evaluate them in an objective manner and provide feedback to the residents regarding their shortcomings.